Marketing, distribution, and consumption of popular music in the face of music piracy and the economic meltdown in Zimbabwe from 2008 to 2019 - Nyahuma, Brian (College of Music, 2022)
The expansion of recording technologies in the world over the past several decades has contributed to an increase in music piracy globally in all forms. As a result, piracy has become a global phenomenon affecting the production, marketing, distribution, and consumption of music. In Zimbabwe, this has been exacerbated by the economic meltdown that the country is facing since 2008. Piracy has emerged to be a problem which has attracted a substantial amount of local and international attention over the past few decades. However, the marketing, distribution, and consumption of popular music in Zimbabwe remains largely uncharted. Thus, this study aims to examine how popular music is marketed, distributed, and consumed in Zimbabwe in the face of music piracy. It also seeks to explore how music piracy has impacted (negatively and positively) on the lives of musicians and record label owners and producers and what these music personnel are doing to combat music piracy. This inquiry is qualitative in nature. Data collection was done using structured and informal interviews as well as document analysis and literature founded research. A concise account of music piracy in select countries of the world in Europe, the Americas, and Africa, in addition to a focus on Zimbabwe, is given through literature review and information gathered through fieldwork to contribute to a new conceptual framework. Results show that music piracy is still a big problem affecting music and has changed the way in which music is marketed, distributed, and consumed in Zimbabwe. The economic situation in the country is also affecting music distribution and consumption with results showing that people would want to deal with basic needs first before embarking on anything else. It also emerged that established musicians are most affected by music piracy than upcoming ones. Key findings from this research indicate that piracy provide upcoming musicians with viable avenues to market themselves. This study is grounded on empirical findings and could be valuable by putting Zimbabwean music on the world map. Further studies should be carried out to see if the same conclusions can be reached